Human body blockage effect on wireless network performance for outdoor coverage - Karrar Shakir Muttair; Mahmood Farhan Mosleh (Institute of Advanced Engineering and Science, 2023)
The rapid development in the field of communications and growing numbers of the population every year stimulate telecommunications companies to develop communications systems to accommodate all users. In this paper, we will study the blockage effect of the student body on the propagation of the signals in the external wireless network. We took various numbers of the student density on the campus to know the extent it affects especially in crowded environments. The student body structure and buildings are designed in the college according to the real dimensions by Wireless InSite software. We compared scenarios for the different numbers of student density, we noticed that whenever an increase in the student density in the college will lead to increased path loss and delay spread time. In addition, note there is a gradual decrease in the received power (RP) if there is no student density highest RP is -28.2 dBm, when there are 300 students highest RP is -34.7 dBm, and when there are 600 students highest RP is -36.5 dBm. The reasons are that signals path spread inside the college will be passing through several collisions whether student body blockage or buildings that are built from different materials.